TANGGUNG JAWAB PELAKU USAHA TERHADAP KELALAIAN PENGOLAHAN BAHAN MAKANAN DALAM PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN - Dwi Anjani, Ni Wayan Cinthya; Yustisia Utami, Putu Devi (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 04 (2024), 2024)
This research was conducted to determine legal protection for consumers who consume inappropriate food due to negligence of business actors and to determine the responsibility of business actors for consumer losses due to negligence in processing food ingredients. Furthermore, this research uses normative research methods with the statute approach and the case approach. The results of this research show that efforts that can be made to guarantee protection for consumers from negligence by business actors in processing food ingredients include providing guarantees for consumer rights and prohibiting regulations for business actors in carrying out their business as well as providing efforts to resolve disputes through litigation and non-litigation. For losses experienced by consumers, business actors must be responsible by providing compensation. In terms of criminal liability, there is a legal vacuum where in Law Number 1 of 2023 on Job Creation, Law Number 18 of 2012 on Food, and Law Number 8 of 1999 on Consumer Protection there is no phrase "due to negligence" as an indication of a criminal act of negligence. Liability of the business actor can only arise if the business actor is proven guilty of the claims filed by the consumer.